Positive Thinking and Its Relationship to the Organizational Performance of Sports Activity Supervisors in the Directorates of Education in the Middle Euphrates - Teba Hashem Adham; Nihad Muhammad Alwan (Indian Journal of Forensic Medicine & Toxicology, 2021)
The positive scientific and logical thinking stage towards building the future vision in organizationalperformance and elevating the workers their ideas, opinions and proposals to the top of the administrativedealings that reflect the organizational culture to which it belongs in organizing the administration and thepositive work of the supervisors of sports activity as successful managers are keen to stay near the fieldsof actual work, as they consider their regular meetings with the cadres working with them a vital factorfor the success of their work, the research aims to identify the relationship of positive thinking with theorganizational performance of the supervisors of sports activity in the directorates of education in the MiddleEuphrates. Karbala, and Diwaniyah) for the 2020 season, the researchers used the descriptive approachand the research community was destroyed from (104) supervisors of sports activities, and the researchersprepared a positive thinking scale consisting of (37) items, and the organizational performance scale consistsof (38) paragraphs and the percentages, arithmetic and hypothetical average were calculated. Finding thereliability coefficient using the half-segmentation method and (Cronbach’s Alpha) to find out the stability ofthe test and the Pearson correlation coefficient for validity of the discrimination of the paragraphs and thet-test